Roles of Microglial and Monocyte Chemokines and Their Receptors in Regulating Alzheimer's Disease-Associated Amyloid-β and Tau Pathologies - Guedes, Joana R.; Lao, Taotao; Cardoso, Ana L.; El Khoury, Joseph (Frontiers in Neurology, 2018)
Chemokines and their receptors have been shown to affect amyloid-β (Aβ) and tau pathologies in mouse models of Alzheimer’s disease (AD) by regulating microglia and monocyte-associated neuroinflammation, microglial movement and monocyte recruitment into the brain. These cells in turn can promote and mediate Aβ phagocytosis and degradation and tau phosphorylation. In this review we discuss published work in this field in mouse models of AD and review what is known about the contributions of microglial and monocyte chemokines and their receptors to amyloid and tau pathologies. We focus on the roles of the chemokine/chemokine receptor pairs CCL2/CCR2, CX3CL1/CX3CR1, CCL5/CCR5, CXCL10/CXCR3 and CXCL1/CXCR2. We also highlight important knowledge gaps in our understanding of such roles. A full understanding of chemokines and their receptors functions in AD may guide the development of novel immunotherapies for this devastating disease.